Modifications of the Fund's Conditionality Framework : Application to the Policy Support Instrument. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
In connection with its recent review of the GRA Lending Toolkit and Conditionality-Reform Proposals, the Executive Board decided that the Fund would move to a review-based approach to monitor the implementation of structural reforms in the context of Fund-supported programs, including under PRGF or ESF arrangements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Conditionality Framework; Fund; PP; Reform Proposal; Reform